2015
DOI: 10.1155/2015/463694
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Death after Being Thrown from Window by Brother with Autism: Defenestration, an Emerging High-Risk Behavior

Abstract: Children diagnosed with autistic spectrum disorders (ASD) may have serious behavioral problems such as aggression, self-injury, and violence. However, the literature on ASD either overrules any correlation between aggression and ASD or maintains the fact that the efforts to link them have so far been inconclusive. Although severe forms of violence are extremely rare in children with autism, there are a few cases reported in the literature with significant harm to siblings. We hereby report an 8-year-old boy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies have found that autism was associated with a variety of health-related risky behaviors (HRB), which may have adverse effects on their health and quality of life [ 6 8 ]. These behaviors including aggression and violence, smoking, alcohol and drug addiction, sexual behaviors related to accidental pregnancy or sexually transmitted infections, unhealthy eating habits, and lack of exercise may cause psychosomatic injuries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that autism was associated with a variety of health-related risky behaviors (HRB), which may have adverse effects on their health and quality of life [ 6 8 ]. These behaviors including aggression and violence, smoking, alcohol and drug addiction, sexual behaviors related to accidental pregnancy or sexually transmitted infections, unhealthy eating habits, and lack of exercise may cause psychosomatic injuries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports have shown that a late diagnosis of ASD is associated with a higher risk of offending [ 26 30 ]. It has also been reported that a lack of appropriate treatment and supervision is a risk factor for violent behavior in patients with ASD [ 31 33 ]. In a review pertaining to patients with ASD and the criminal justice system, King and Murphy [ 34 ] found that there were some similarities between the difficulties faced by people with ASD and people with intellectual disabilities within the criminal justice system; however, they demonstrated that people with ASD were not overrepresented in the criminal justice system.…”
Section: Introductionmentioning
confidence: 99%